2009
DOI: 10.1542/peds.2008-1378
|View full text |Cite
|
Sign up to set email alerts
|

Morbidities and Hospital Resource Use During the First 3 Years of Life Among Very Preterm Infants

Abstract: Most very preterm infants born in Finland survived without severe morbidities and required relatively little hospital care after the initial discharge. However, those with later morbidities had a long initial length of stay and more readmissions and outpatient visits during the 3-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
4
26
0
2
Order By: Relevance
“…[1][2][3][4][5] These rehospitalizations are accompanied by significant morbidity and sometimes mortality 4,5 and occur at high cost to the family as well as society. 4,6 Strategies such as the use of prophylaxis for respiratory syncytial virus infections 7 and comprehensive follow-up care 8 are designed to reduce these rehospitalizations.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] These rehospitalizations are accompanied by significant morbidity and sometimes mortality 4,5 and occur at high cost to the family as well as society. 4,6 Strategies such as the use of prophylaxis for respiratory syncytial virus infections 7 and comprehensive follow-up care 8 are designed to reduce these rehospitalizations.…”
mentioning
confidence: 99%
“…[6][7][8][9] During the first 3 years of life, the need for hospital care clearly decreases more in very preterm children without prematurity-related morbidities than in very preterm children with these morbidities. 10 Only a few studies have explored the costs of hospitalizations of very preterm children after the first year of life, and other health care costs have barely been evaluated. In the study by Petrou et al, 8 the hospitalization costs significantly decreased after the first year.…”
mentioning
confidence: 99%
“…Various studies across the world have tried to ascertain the neonatal risk factor for post NICU discharge hospital re-admission [1][2][3][8][9][10][11][12][13]. Ambalavanan, et al in their recent publication using classification and regression tree analysis concluded that neonates who spent > 120 days during their NICU admission for pulmonary reasons had a 66% re-hospitalization rate compared to 42% without such stay [3].…”
Section: Risk Factors For Hospital Re-admissionmentioning
confidence: 99%
“…Re-hospitalization after initial discharge from NICU for preterm infants has been examined in various settings across the world [1][2][3][4][5][6][7][8][9][10][11][12][13]. Reasons for re-hospitalizations in extreme preterm infants can be related either to medical (bronchiolitis, lower-respiratory tract infection, asthma, reflux disease) or to surgical (PEG related problems, V-P shunt related issues, hernia repair) causes.…”
Section: Introductionmentioning
confidence: 99%